Methodical Approach to the Supply Chain Strategy Development for Large Enterprises Based on a Balanced Indicator System - S. Rakhmanova, Marina; V. Kryukov, Vladimir; A. Bedrachuk, Ilya (International Journal of Supply Chain Management, 2020)
The article describes a methodological approach to the supply chain strategy development, consisting of seven stages and allowing taking into account the specific nature of the activities of large enterprises. This approach includes one of the most important stages in the supply chain strategy development, that is, its evaluation. Many authors exclude this stage during consideration. The use of a balanced indicator system (hereinafter - the BIS) in the supply chain strategy development for the enterprise allows taking into account a greater number of performance indicators for a detailed analysis of a large enterprise, which helps to identify problem areas in their activities in exchange. The article presents the developed methodology for assessing the effectiveness of the supply chain strategy for large enterprises based on the BIS: we improved the traditional performance indicators and developed additional indicators within each prospect of the modified BIS. The author’s methodology includes the development of integrated indicators of the effectiveness of the supply chain strategy based on expert assessment, with the help of which the supply chain strategy is evaluated from the perspective of all the prospects considered within the framework of the modified BIS.